RESPONSE OF KHARIF GREENGRAM (VIGNA RADITA L. WILCZEK) TO SULPHUR AND PHOSPHORUS FERTILIZATION WITH AND WITHOUT BIOFERTILIZER APPLICATION - H. R. PATEL; H. F. PATEL; V. D. MAHERIYA; I. N. DODIA (The Bioscan, 2012)
The experiment was conducted with three levels of sulphur from gypsum (0, 20 and 40kg ha-1), two levels of phosphorus (0, 20, 40kg ha-1) and two levels of PSB inoculation (inoculation and uninoculation) was conducted to study the response of kharif greengram (Vigna radita L. Wilczek) to sulphur and phosphorus fertilization with and without biofertilizer application . 40 kg S ha-1 recorded significantly maximum number of branches plant- 1(4.48). plant spread (34.10), number of nodules plant-1(16.46), dry matter plant-1(9.27g), seed yield (1486.08 kg ha-1), stalk yield (2161.79 kg ha-1) and protein content (22.46%) as well as gave the highest net realization (Rs.28,440 ha-1) with a net ICBR (1: 27.63). Similar trend was also observed in phosphorus application. 40 kg ha- 1 phosphorus recorded significantly maximum number of branches plant-1(4.48), plant spread (34.15), number of nodules plant-1(16.66), dry matter plant-1 (8.74), seed yield (1435.95 kg ha-1), stalk yield (2197.55 kg ha-1) and protein content (21.34%) as well as gave the highest net realization (Rs.26,996 ha-1) with a net ICBR (1:5.03). PSB inoculation significantly affected most of the growth parameters, yield attributes and yield, quality parameters. PSB inoculation recorded significantly the highest seed yield (1350.19 kg ha-1) and stalk yield (2153.29) over uninoculation, also gave the highest net return (Rs. 25180 ha-1) with net ICBR (1:111.27) as compared to uninoculation.